PENGARUH SKEMA KOMPENSASI, SELF EFFICACY DAN PENALARAN MORAL TERHADAP SLACK BUDGETING - Nayang Helmayunita; Ade Elsa Betavia (Jurnal Aplikasi Akuntansi, 2019)
This study aims to examine the effect of compensation schemes, self efficacy and moral reasoning on slack budgeting. In this study the hypothesis is proposed that in the slack inducing compensation scheme the slack budgeting will be greater than using the truth inducing compensation scheme, then managers with low self efficacy will do slack budgeting compared to those with high self efficacy. It is also proposed that the individual with low moral reasoning will do slack budgeting rather than the individual with high moral reasoning. The research design in this study was a quasi 2 x 2 laboratory experiment, with Accounting students who had sat in the 5th semester of Padang State University as lower level managers who participated in budgeting. The statistical method used to test the hypothesis is two-way ANOVA. This study provides results that the compensation scheme can affect slack budgeting actions, self efficacy has no effect on slack budgeting actions, and the interaction between slack inducing compensation schemes with low self efficacy has no effect on slack budgeting actions. Moral reasoning affects slack budgeting actions, and at lower level managers who have low levels of moral reasoning and low levels of self efficacy, interactions with slack inducing compensation schemes affect slack budgeting actions. The results of this study can contribute in the management accounting literature related to budgetary slack and its causal factors. Keyword: Slack Budgeting, Compensation Schemes, Self Efficacy, and Moral Reasoning.